2020
DOI: 10.1039/d0ma00290a
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the ORR selectivity for H2O2 electrogeneration by modification of Printex L6 carbon with 1,4-naphthoquinone: a theoretical, experimental and environmental application study

Abstract: H2O2 is one of the most popular precursors used in the production of hydroxyl radical. The compound is employed in advanced oxidative processes (AOPs) for the removal of recalcitrant organic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 63 publications
0
3
0
1
Order By: Relevance
“…This compartment is constantly pressurized to 0.2 bar of O2 gas. The pressure of 0.2 bar of the O 2 gas is already widely used in other studies by our research group [26][27][28], and this is the optimal condition used, since it constantly keeps the GDE saturated with oxygen. And so, the limitation of mass transfer by O2 is eliminated.…”
Section: Fabrication and Electrochemical Study Of Gdesmentioning
confidence: 99%
See 1 more Smart Citation
“…This compartment is constantly pressurized to 0.2 bar of O2 gas. The pressure of 0.2 bar of the O 2 gas is already widely used in other studies by our research group [26][27][28], and this is the optimal condition used, since it constantly keeps the GDE saturated with oxygen. And so, the limitation of mass transfer by O2 is eliminated.…”
Section: Fabrication and Electrochemical Study Of Gdesmentioning
confidence: 99%
“…In 360 min, the energy consumption was 9.81 kWh kg -1 to mineralize ~85% of ciprofloxacin [39]. Kronka et al (2020), using a GDE modified with 1.0% of 1,4-naphthoquinone in the paracetamol drug degradation via PEF treatment at 75 mA cm -2 for 180 min obtained an EC value of 6.35 kWh kg -1 and 42% of mineralization [27]. As can be seen, unmodified or modified GDE applied in treatment processes via PEF have lower energy consumption values compared to other techniques used in EAOP.…”
Section: 𝐸𝐶 =mentioning
confidence: 99%
“…Os materiais de carbono amorfo (conhecido em inglês como carbon black) do tipo Printex são empregados em muitos estudos e apresentados como materiais altamente reativos para a redução de O2, obtendo alta quantidade de carbono sp 2 , alta área superficial, hidrofobicidade, excelente condutividade e um grande número de grupamentos funcionais em sua composição, sendo reportados na literatura os melhores materiais a base de carbono para estudo da RRO [2,12,14,21,31,[45][46][47][48]. Os carbonos do tipo Printex são gerados a partir da combustão incompleta ou decomposição térmica de produtos derivados do petróleo [14,49,50].…”
Section: Eletrocatalisadoresunclassified
“…Similarly, Rocha et al (2020) examined the effect of different quinones where the object of their study was mainly targeted at enhancing H2O2 electrogeneration without effectively applying the technique toward water and wastewater 61 treatment[41]. Unlike the aforementioned studies, in the study reported byKronka et al (2020),…”
mentioning
confidence: 99%